2018
DOI: 10.7589/2017-09-238
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Two Cocirculating Canine Distemper Virus Strains in Mesocarnivores From Northern Colorado, Usa

Abstract: Canine distemper virus (CDV) is a highly contagious pathogen that principally infects wildlife and domestic carnivores. Peridomestic species such as raccoons ( Procyon lotor) experience outbreaks with high mortality. Clinical signs of infection include anorexia, fever, respiratory infection, and neurologic complications. Although not zoonotic, CDV poses a high risk to unvaccinated domestic animals and the conservation of endangered species. During 2013-16, we opportunistically collected wild and domestic carni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…It is possible that the slightly lower percent identity for the swine IAV is a result of relative paucity of sequence data available for 2019 swine IAV at this time. The CDV America II lineage, the classification of CDV in our study, is a common lineage found in North American wildlife, 54 and is consistent with the collection of this sample from a raccoon in Kentucky. The sequences for IBV and PRRSV were highly similar to the known sequences of those isolates.…”
Section: Discussionsupporting
confidence: 87%
“…It is possible that the slightly lower percent identity for the swine IAV is a result of relative paucity of sequence data available for 2019 swine IAV at this time. The CDV America II lineage, the classification of CDV in our study, is a common lineage found in North American wildlife, 54 and is consistent with the collection of this sample from a raccoon in Kentucky. The sequences for IBV and PRRSV were highly similar to the known sequences of those isolates.…”
Section: Discussionsupporting
confidence: 87%
“…It is possible that the slightly lower percent identity for the swine-origin influenza is due to a relative paucity of sequence data available for 2019 swine-origin IAV at this time. The CDV America II lineage, the classification of CDV in this study, is a common lineage found in North American wildlife 42 and is consistent with the collection of this sample from a raccoon in Kentucky. The sequences for IBV and PRRSV were highly similar to the known sequences of those isolates.…”
Section: Discussionsupporting
confidence: 85%
“…Virus detection a. Virus isolation (MDCK, Vero cells-SLAM B95a, etc) Virus Gold standard test Highly sensitive, helpful for generating virus repository (Require live virus titre, specific cell line and cell culture facilities) [ 7 ] [ 107 ] [ 120 ] Direct ELISA CDV antigen Detects antigen in serum [ 119 ] b. Antigen detection Sandwich ELISA H protein High specificity Detection and quantitation [ 91 ] F protein Efficient in field application with fecal and serum samples [ 148 ] Sandwich dot ELISA Virus Epidemiological surveillance [ 65 ] LFA F protein Practically applicable in the field for quick diagnosis [ 1 ] c. Nucleic acid detection RT-PCR N gene Standard laboratory test [ 39 ] One-step nested-RT-PCR N gene 100-fold sensitivity than RT-PCR and nested PCR [ 56 ] Double step real time-RT-PCR N gene Highly sensitive and specific Quantitate viral load in clinical samples [ 34 ] One-step real-time RT-PCR -- To study viral replication and kinetics of viral RNA load in infection …”
Section: Available Diagnostic Tools For CDVmentioning
confidence: 99%